Pembuatan Web Pembanding Fashion Wanita - Nathania, Yvonne; Andjarwirawan, Justinus; Rostianingsih, Silvia (Jurnal Infra, 2016)
The development of todays fashion world has increased. The number of sellers who sell clothes online through social media be a sign that the fashion world today has grown. Besides through social media, online shopping sites also sell a wide range of fashion products with items, brands and prices vary. The number of different types of items that make the customer the trouble to compare the prices item.. Therefore, in order to facilitate the customers to compare prices between items especially womens fashion, it is necessary to form a portal site that is able to collect a variety of information contained in this online site among Lazada, Zalora, and Tokopedia. the information in the form of price, items name, product description and origin of the site.The system has the ability to scrape data from Tokopedia, Lazada and Zalora using web scraping and web services. User can easily compare between products and systems also provide a simple recommendation system price comparison of the products being compared.Overall the systems can help users to compare between womens fashion and display products with lowest price. System also can display search results according to the keywords entered by users. In the process of data collection, web scraping takes longer time to retrieve data than data retrieval using web service.